Is it possible to estimate urethral mobility based on maximal urethral closure pressure measurements? - Nováková, Z; Mašata, J; Švabík, K (Ceska gynekologie, 2019)
OBJECTIVE: Is it possible to estimate urethral mobility based on MUCP measurements? DESIGN: Retrospective study. SETTING: Department of Gynecology and Obstetrics, 1st Medical Faculty, Charles University, General Teaching Hospital, Prague. METHODS: This retrospective study included 567 patients from three prospective studies within years 2002 to 2009. Ultrasound examination was performed in 560 of them and maximal urethral closure pressure (MUCP) values were measured in 507 women. The MUCP was defined as the difference between maximum urethral pressure and bladder pressure. An ultrasound examination was performed using the transperineal approach in accordance with the recommendations of the German Urogynecology Working Group and ICS, IUGA terminology. The mobility was expressed as a distance between the position at rest and at the maximal Valsalva manoeuvre. Data were summarized as mean and median, with SD and quantile range for measures of variability. Either a matched pairs t-test or Wilcoxon test was used for statistical evaluation. RESULTS: Mean MUCP was 47.4 cm H2O (SD 22.2, first quantile 32, third quantile 62). Mean urethral descent was 20.6 mm (SD 8.2, first quantile 14.9, third quantile 25.6 mm). Using regression analysis there was an increase in urethral descent; this difference is statistically significant. For a MUCP increase of 10 cm H2O we could estimate an increase in urethral descent of 1.1 mm. CONCLUSION: We established a statistically significant relationship between urethral descent and MUCP. Unfortunately those differences are not clinically relevant, especially for MUCP over 20 cm H2O. For MUCP below 20 cm H2O low urethral descent is more likely. Clinical use of MUCP as predictor of urethral descent is limited due to the high variability involved.
Keywords: stress urinary incontinence; Urethra; urodynamic study; Retrospective Studies; těhotenství; maximum urethral closure pressure; výsledek terapie; urodynamika; Urinary Bladder; Prospective Studies; močový měchýř; descent of the urethrovesical junction; MUCP; uretra; ženské pohlaví; Urologic Surgical Procedures; stresová inkontinence moči; retrospektivní studie; prospektivní studie; Humans; Pregnancy; Urodynamics; urologické chirurgické výkony; Urinary Incontinence, Stress; Female; Treatment Outcome; lidé